Insufficiency of Medical Care for Patients with Acute Respiratory Failure - A. V. Dats; L. S. Dats; I. V. Khmel'nitskii (Общая реаниматология)
The purpose of the research: to analyze insufficiency of medical care for patients with acute respiratory failure in the ICU.Materials and methods. It was a retrospective study of 160 patients' medical records (age from 15 to 84 years) with acute respiratory failure (ARF) hospitalized in the ICUs of 24 regional and municipal hospitals of the Irkutsk Oblast. Medical records were provided by the Territorial Fund of Compulsory Medical Insurance of citizens of Irkutsk region.The results. The basic defects in conducting mechanical ventilation were associated with improper lung function evaluation, microbiological tests of sputum and radiology. ARF was not diagnosed in 32 of 160 ICU patients (20%). In 23% of cases the causes of ARF were not diagnosed. The greatest part of the defects in the treatment of patients with acute respiratory failure was found during the treatment of hypoxemia: no recovery of the respiratory tract patency, no prescription of oxygen for hypoxemia, no mechanical ventilation for persistent hypoxemia on the background of maximum oxygen supply and late switching to mechanical ventilation at the stage of hypoxic cardiac arrest.Conclusions. The use of pulse oximetry alone in the absence of arterial blood gas analysis in 98% of patients with acute respiratory failure and failure to perform the lung X-ray and/or MSCT imaging in 21% of patients were accompanied by a high level of undiagnosed acute respiratory distress syndrome (78%), lung contusion (60%), pulmonary embolism (40%), cardiogenic pulmonary edema (33%), and nosocomial pneumonia (28%). Defects of treatment of patients with ARF in 46% of cases were caused by inadequate management of hypoxemia associated with the recovery of the respiratory tract patency, prescription of oxygen, and mechanical ventilation.